EVALUATION OF SOME HEAVY METALS AROUND MAJOR DUMPSITES IN BOLARI WEST WARD, GOMBE STATE, NIGERIA - Magaji, Buhari; Muhammad Salim , Isah; Shehu, Zaccheus (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The levels of heavy metals (Cu, Pb, Zn and Fe in mg/kg) in dumpsite soils from Bolari west ward, Gombe State, Nigeria were assessed with respect to distance from the dumpsites. The heavy metal concentrations were determined by atomic absorption spectrophotometry. The results show that iron had the highest concentration in all the soils, and copper had the lowest concentration. The concentration of the heavy metals can be represented in the following order: sample A: Fe > Zn > Cu, and sample B and D: Fe > Zn. However, Pb was not found in all the sampling sites and their control samples. The heavy metal concentrations were found to be higher in the dumpsite soils as compared with the control samples. Thus, the metal concentrations decrease with increased distance from the dumpsites. The heavy metals found are higher than the WHO permissible limits for heavy metals in soil.